Pharmacy student perceptions of pharmacist prescribing: A comparison study - Charrois, Theresa; Rosenthal, M.; Hoti, Kreshnik; Hughes, C. (M D P I AG, 2013)
Several jurisdictions throughout the world, such as the UK and Canada, now have independent prescribing by pharmacists. In some areas of Canada, initial access prescribing can be done by pharmacists. In contrast, Australian pharmacists have no ability to prescribe either in a supplementary or independent model. Considerable research has been completed regarding attitudes towards pharmacist prescribing from the perspective of health care professionals, however currently no literature exists regarding pharmacy student views on prescribing. The primary objective of this study is to examine pharmacy student’s opinions and attitudes towards pharmacist prescribing in two different settings. Focus groups were conducted with selected students from two universities (one in Canada and one in Australia). Content analysis was conducted. Four main themes were identified: benefits, fears, needs and pharmacist roles. Students from the Australian University were more accepting of the role of supplementary prescribing. In contrast, the Canadian students felt that independent prescribing was moving the profession in the right direction. There were a number of similarities with the two groups with regards to benefits and fears. Although the two cohorts differed in terms of their beliefs on many aspects of prescribing, there were similarities in terms of fears of physician backlash and blurring of professional roles.